MTOR Inhibition Is Most Beneficial After Liver Transplantation for Hepatocellular Carcinoma in Patients With Active Tumors. Issue 5 (November 2020) - Schnitzbauer, Andreas A.; Filmann, Natalie; Adam, René; Bachellier, Philippe; Bechstein, Wolf O.; Becker, Thomas; Bhoori, Sherrie; Bilbao, Itxarone; Brockmann, Jens; Burra, Patrizia; Chazoullières, Olivier; Cillo, Umberto; et al.
Abstract : Objective: The aim of this study was to evaluate the survival benefit of sirolimus in patients undergoing liver transplantation (LT) for hepatocellular carcinoma (HCC) (exploratory analysis of the SiLVER-trial). Summary and Background Data: Patients receiving LT) for HCC are at a high risk for tumor recurrence. Calcineurin inhibitors have shown evidence to promote cancer growth, whereas mammalian target of rapamycin (mTOR) inhibitors like sirolimus have anticancer effects. In the SiLVER-trial (Clinicaltrials.gov: NCT00355862), the effect of sirolimus on the recurrence of HCC after LT was investigated in a prospective randomized trial. Although the primary endpoint of improved disease-free survival (DFS) with sirolimus was not met, outcomes were improved for patients in the sirolimus-treatment arm in the first 3 to 5 years. To learn more about the key variables, a multivariate analysis was performed on the SiLVER-trial data. Patients and Methods: Data from 508 patients of the intention-to-treat analysis were included in exploratory univariate and multivariate models for overall survival (OS), DFS and a competing risk analysis for HCC recurrence. Results: Sirolimus use for ≥3 months after LT for HCC independently reduced the hazard for death in the multivariate analysis [hazard ratio (HR): 0.7 (95% confidence interval, CI: 0.52–0.96, P = 0.02). Most strikingly, patients with an alpha-fetoprotein (AFP) ≥10 ng/mL and having used sirolimus for ≥3 months, benefited most with regard to OS, DFS, and HCC-recurrence (HR: 0.49–0.59, P = 0.0079–0.0245). Conclusions: mTOR-inhibitor treatment with sirolimus for ≥3 months improves outcomes in LT for HCC, especially in patients with AFP-evidence of higher tumor activity, advocating particularly for mTOR inhibitor use in this subgroup of patients. Clinical Trial Registration: EudraCT: 2005-005362-36 Clinicaltrials.gov: NCT00355862. Abstract : Supplemental Digital Content is available in the text